ANALYSIS OF BRAND IMAGE, PRODUCT FEATURES, AND CELEBRITY ENDORSEMENTS ON VIVO MOBILE PURCHASING DECISIONS - Yendra, Yendra; Hendrayani, Eka; Wulandari, Wulandari; Saragih, Megasari Gusandra; Setiawan, Roy (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
The purpose of this study was to determine the effect of brand image, product features and celebrity endorsement on purchasing decisions for Vivo cellphones at PT. Win Access Telecommunication Medan. This research method is a quantitative research method with a total sample of 90 people. The sampling technique is purposive sampling where only customers who buy Vivo X series mobile phones can be sampled. The model used with Multiple Regression and processed through SPSS Ver, 20.5. The results of the study found that brand image, product features and celebrity endorse had a positive and significant effect both partially and simultaneously on purchasing decisions for Vivo mobile phones at PT. Win Access Telecommunication Medan. The adjusted R Square value is 0.729, which means that 72.9% of purchasing decisions can be obtained and explained by brand image, product features and celebrity endorsements. While the remaining 100% - 72.9% = 27.1% is explained by other factors or variables outside the model, such as brand trust, price and product attributes.